Mini Review: Biologically synthesized nanoparticles as antifungal agents - Siti Nur Amalina, M. S.; Shameli, Kamyar; Teow, Sin Yeang *; Nur Afini, I. (Akademia Baru, 2021)
Fungal infections are affecting millions of people in the world every year. Severity of infections range from superficial mycoses to more chronic systemic mycoses. As more fungi species evolve, emergence of drug resistant strains is becoming a serious concern to the public health. There is now less number of effective antifungal drugs available in the market for treatment of invasive fungal infections. In an effort to combat this escalating issue, the use of nanoparticles as antifungal agent has been proposed and explored. Versatility of nanoparticles and its unique physico-chemical properties are proven beneficial for developing new therapeutic methods in treatment of fungal infections. Nanoparticles produced from biological synthesis have attracted keen interests from researchers, as they are more environmentally friendly, sustainable, cost-effective, and biocompatible. This mini review will provide an insight on the current antifungal studies and discuss the theory behind mechanism of actions of nanoparticles.